Relationships between normal or borderline blood pressure and some neural, endocrine, metabolic and biophysic parameters in women and men - Yuliya V. Vovchyna; Nataliya M. Voronych; Walery Zukow; Igor L. Popovych (Kazimierz Wielki University, 2016)
Vovchyna Yuliya V., Voronych Nataliya M., Zukow Walery, Popovych Igor L. Relationships between normal or borderline blood pressure and some neural, endocrine, metabolic and biophysic parameters in women and men. Journal of Education, Health and Sport. 2016;6(2):163-182. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.2525023 http://ojs.ukw.edu.pl/index.php/johs/article/view/3396 https://pbn.nauka.gov.pl/works/715715     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 21.02.2016.     RELATIONSHIPS BETWEEN NORMAL OR BORDERLINE BLOOD PRESSURE AND SOME NEURAL, ENDOCRINE, METABOLIC AND BIOPHYSIC PARAMETERS IN WOMEN AND MEN   Yuliya V. Vovchyna1,2, Nataliya M. Voronych2, Walery Zukow3, Igor L. Popovych4   1Sanatorium "Kryshtalevyǐ Palats" SAD, Truskavets', Ukraine     yulija_if@mail.ru 2Department of Normal Physiology, National Medical University, Ivano-Frankivs'k, Ukraine 3Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   w.zukow@ukw.edu.pl 4Laboratory of Experimental Balneology, OO Bohomolets' Institute of Physiology NAS, Truskavets'-Kyiv, Ukraine     i.popovych@biph.kiev.ua   Abstracts Background. We conduct a systematic study of the effect of balneotherapy spa Truskavets (Ukraine) on blood pressure. The aim of this study is to elucidate the links between normal and marginal blood pressure, on the one hand, and some neural, endocrine, metabolic and biophysical factors on the other. Material and research methods. We recorded twice at ten women and ten men aged 33-76 years without clinical diagnose Blood Pressure, Heart Rate, heart rate variability (HRV), electroencephalogram (EEG), electro-skin conductance acupuncture points (ESCAP) Pg(ND), TR(X) and MC(AVL), determined the rate of electronegative nuclei of buccal epithelium (named as Electrokinetic Index) as well as plasma levels of Calcitonin, Testosterone, Cortisol, Triiod-thyronin, Cholesterol, Uric Acid, Chloride, Phosphate, Sodium, Potassium, Calcium and Magnesium. Results. Observed contingent characterized generally normal for a particular age or borderline high blood pressure, predominantly diastolic. In the final regression model were included 4 metabolic parameters (Cholesterol, Uric Acid, Phosphate and Calcium), 3 neural (α-rhythm Index as well as RMSSD and Triangulary Index as markers of Vagal tone) and ESCAP  TR(X) Right as marker activity of endocrine system, which taken together determines Systolic Blood Pressure on 77%. Diastolic Blood Pressure determined on 74% by 7 neural parameters (4 HRV markers of Vagal and Sympathetic tone as well as α-rhythm Amplitude and Deviation and θ-rhythm Frequency), 2 biophysic parameters (ESCAP  TR(X) Right and Electrokinetic Index as marker of biological age) as well as Chloride and Hender. Conclusion. Normal and marginal blood pressure determined by some neural, biophysical and metabolic factorss well as Hender.   Keywords: blood pressure, HRV, EEG, hormones, electrolytes, relationships.